Cries in the night ; Person of interest - Webb, Debra (Sydney, NSW : Harlequin Mills & Boon, 2022)
Cries in the night: Haunted by her daughter's cries in the night, Melany Jackson will stop at nothing to track down her child. And if that means joining forces with Ryan Braxton - the man she still loves - then so be it. Melany and Ryan must quickly unravel the clues in the case. But what Melany fears more than her attraction to Ryan is that he might discover her child is also his.
Person of interest: By performing facial reconstruction surgeries for the CIA, Dr. Elizabeth Cameron provided new identities for agents whose covers had been blown. But someone wanted one in particular dead - and now Elizabeth is in jeopardy. As the danger escalates, her only hope rests with Agent Joe Hennessy, the one man she swore never to set eyes on again.
Title from title screen.
Mode of Access: Available online.
Keywords: Contemporary romance; Fiction - Romance - Contemporary; Fiction - Suspense; Electronic books; Romance fiction